Aggregation of plaque disclosing agent in a dentifrice - Silva, Débora Dias da (2004)
Dental plaque removal is an important issue in health promotion. Toothbrushing is one of the main methods employed for such purpose, since it can prevent dental caries by means of the fluoride present in the dentifrice. Dentifrices might contain plaque disclosing agents and thus allow dental plaque observation. The aim of this study was to assess whether utilization of a plaque disclosing agent interfered with plaque removal among adolescents, as well as the difference between utilization of erythrosine tablets and dentifrices containing plaque disclosing agent. The sample was composed of 62 students from Piracicaba, SP, Brazil, aged 12 to 14 years old, divided into 3 groups: G1 or control group (toothbrushing without plaque disclosure); G2 (plaque disclosing with an erythrosine tablet and toothbrushing) and G3 (toothbrushing with dentifrice containing plaque disclosing agent). After toothbrushing, disclosure of the remaining dental plaque was performed in all groups with a fuchsin tablet and measured through the Simplified Oral Health Assessment Index (OHI-S), in two stages with a 2-month interval between them. The analysis of variance (ANOVA) showed that there was no difference in the OHI-S index between the groups (p>;0.05), however the G3 displayed a higher proportion of students with plaque reduction (23%) than G2 (21%), besides the smallest difference in the mean remaining dental plaque. There was no difference between groups; however, it was suggested that the dentifrice with plaque disclosing agent had positive results in relation to the erythrosine tablet, even though the small sample size may have interfered with the results, indicating the need of complementary studies.